The Employment Levels in the European Union and in the Republic of Moldova: A Comparative Analysis - Alic Birca; Alla Mamaliga (CES Working Papers, 2016)
This article addresses the issue of employment. Employment policy was and still is a rather important issue that has always drawn economists' attention and has always been on the business agenda of central public bodies. The global economic crisis in 2008 influenced the employment rate of the workforce in most countries, including the EU Member States. Employment has been a problem for the Republic of Moldova since its independence. In order to increase the employment levels of the workforce, many countries have undertaken a series of active measures that have brought good results. The European Union itself, in the 2020 strategy aims at increasing the level of employment of the workforce up to 75% for people 20-64 years of age. This article describes the employment situation in the European Union and in the Republic of Moldova by highlighting the current disparities.
Keywords: F15; F16; J62; J64; 330; labour market; employment; labour force; employment rate